Analysis of Flexural Behaviour of Hybrid Stainless Steel I-Beams - Sameer, Shaik; Rama Prasad, C.Venkata Siva; Reddy, B. Sudharshan (Journal of Neonatal Surgery, 2025)
This study presents a comprehensive numerical investigation into the flexural behavior of Hybrid Stainless Steel (HSS) I-beams using the finite element software ABAQUS. The hybrid sections incorporate Duplex Stainless Steel (DSS) and Lean Duplex Stainless Steel (LDSS), aiming to balance strength, ductility, and cost efficiency. The research validates the finite element (FE) models against experimental results from literature and evaluates the influence of geometric parameters such as flange and web slenderness on moment capacity and failure modes. Parametric studies reveal that hybridization significantly enhances moment resistance while mitigating local buckling. The study further compares numerical results with predictions from the European Standard EN 1993-1-4 and the Direct Strength Method (DSM). Findings demonstrate that DSM provides more accurate and conservative predictions for hybrid sections, making it a viable design approach for HSS beams. The results contribute to a deeper understanding of the flexural performance of hybrid stainless steel beams and support the development of efficient and reliable design methods for stainless steel structural members.